Comparison of the Arterial PaCO2 Values and ETCO2 Values Measured with Sidestream Capnography in Patients with a Prediagnosis of COPD Exacerbation - Gökhan İşat; Tuba Cimilli Öztürk; Özge Ecmel Onur; Serdar Özdemir; Ebru Ünal Akoğlu; Fatma Tokgöz Akyıl; Hacer Kuzu Okur (Avicenna Journal of Medicine, 2023)
Background Aim of this study is to investigate whether end-tidal carbon dioxide (ETCO2) values can be used instead of partial pressure of carbon dioxide (PaCO2) values in guiding treatment, and determining treatment benefits in patients that received a pre-diagnosis of chronic obstructive pulmonary disease (COPD) exacerbation at the emergency department.